Effect of Fibres Length on Acoustic Properties of Betel Nut Husk (Areca Nut Husk) Fibers–Reinforced Epoxy Composites - Putri Pratiwi; Hendriwan Fahmi; Georgery Saputra (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2019)
The objective of this research is to determine the acoustic properties (sound absorption coefficient) in a various length of betelnut fibers. Betel nut fibers were obtain from local plantation in Padang as agro waste material and potentially used as sound absorber. In this study, we used betel nut fibers as a filler of composites and epoxy resin as a matrix using the ratio of volume fraction of 40% : 60%. We used three variations of fibers length such as 1 cm, 2 cm and 3 cm. The sound absorption coefficient of composites was studied using impedance tube method with 1000 Hz, 1500 Hz, 2000 Hz, and 2500 Hz frequency. The results showed that composite using 3 cm fibers length of betelnut husk would give the optimum sound absorption coefficient at 1500 Hz frequency, but composites with 1 cm fibers length showed a great performance as sound absorbing materials at various sound frequencies that have been tested. From this research shown that betelnut fiber composite give the optimum sound absorption coefficient at various fibres length and can be used as sound absorption materials, based on ISO standard 11654:1997.